Analisis Perilaku Belajar Siswa Kelas X ADP SMK Muhammadiyah 2 Pekanbaru - Asri Neli Putri; Khairi Murdy (Jurnal Ecogen, 2019)
Abstract: This type of research is qualitative and data collection techniques in this study are 3: 1) Observation Techniques, 2) Interview Techniques, and 3) Documentation. Data analysis techniques using data reduction, data presentation and triangulation. The formulation of the problem in this study is how is the Analysis of the Behavior of Class X ADP 3 and ADP 4 Students at SMK Muhammadiyah 2 Pekanbaru in the Learning Process. The results showed that in general of the five indicators: observation, associative thinking and memory, rational and critical thinking, inhibition, and appreciation can be good categories in student learning behavior, only a small proportion of students who still do actions that are not in accordance with student learning behavior in the learning process, it is necessary to take the attention of parents and teachers to monitor student learning behavior so that students can apply the rules that have been determined by the school.Keyword: analysis, behavior learning, student